The vascular risk factors and vascular neuropathology in subjects with autopsy‐confirmed dementia with Lewy bodies. (6th February 2022) - Chen, Zhi‐Chao; Gan, Jinghuan; Yang, Yaqi; Meng, Qingbo; Han, Jiuyan; Ji, Yong
Abstract: Background: The frequency of vascular risk factors (VRFs) and the relationship between vascular pathology and cognitive function in neurodegenerative disease remains incompletely understood. Objective: The purpose of this study was to describe the frequency of VRFs and vascular pathology and explore the relationship between vascular pathology and cognitive function in dementia with Lewy bodies (DLB). Methods: This study included 363 autopsy‐confirmed DLB and 753 Alzheimer's disease (AD) patients from the National Alzheimer's Coordinating Center (NACC) database. We used chi‐squared test and analysis of variance to compare the VRFs and related factors in DLB and AD. Multinomial logistic regression and Spearman's correlation test were used to examine the relationship between vascular pathology and cognitive function. Results: No significant differences of VRFs were identified between DLB and AD. Alzheimer's disease patients had higher rates of microinfarcts (23.5% vs. 16.3%, p = 0.005) and moderate to severe amyloid angiopathy (45.9% vs. 36.1%, p = 0.002). In DLB patients, only cerebral amyloid angiopathy (CAA) pathology was negatively correlated with memory domain (r = −0.263, p < 0.001) and language (r = −0.112, p = 0.034). The rates of APOE ε4 allele carriers (60.0% vs. 44.9%, p = 0.004) and CAA pathology (45.9% vs.23.4%, p < 0.001) were much higher in the group with an intermediate likelihood of DLB than in the group with a high likelihood. There was a negative correlation between CAA pathology and memory (logical memory) in the group with an intermediate likelihood of DLB. Conclusion: No difference of VRFs was identified between autopsy‐confirmed DLB and AD. Cerebral amyloid angiopathy was shown to be an important pathology in DLB, which specifically correlated with memory and language. The groups with high and intermediate likelihood of DLB differed in terms of CAA pathology, and CAA pathology may play an important role in the development of DLB. Key points: No difference of VRFs was identified between autopsy‐confirmed DLB and AD. CAA was shown to be an important pathology in DLB, which specifically correlated with memory and language. The rate of CAA pathology was much higher in the group with an intermediate likelihood of DLB than in the group with a high likelihood.